CpA/CpG methylation of CiMDA5 possesses tight association with the resistance against GCRV and negatively regulates mRNA expression in grass carp, Ctenopharyngodon idella. Issue 1 (January 2015) - Shang, Xueying; Su, Jianguo; Wan, Quanyuan; Su, Juanjuan
Highlights There are methylated CpA loci in CGIs located in the first exon of CiMDA5. Methylation levels were extremely higher in the susceptible group at four CpA/CpG loci. CiMDA5 expression was negatively regulated by DNA methylation. Four significant CpA/CpG loci consisted of a densely methylated element (DME). Most of the CpA/CpG loci were unmethylated in CGIs.